Feeding a grape seed extract extends the survival of the red flour beetle Tribolium castaneum under heat-stress depending on nrf-2, jnk-1, and foxo-1 homologous genes but independent of catechin monomers - Grünwald, Stefanie; Fast, Anna; Müller, Karen; Boll, Michael; Kler, Adolf; Bonnländer, Bernd; Wenzel, Uwe; Justus Liebig University Giessen (My University, 2014)
Besides caloric restriction, a diet rich in fruits and vegetables is believed to delay the ageing process thus providing a powerfull tool in preventive medicine. To investigate underlying interactions between food ingredients and genes simple models, such as the red flour beetle Tribolium castaneum, appear especially constructive. Here we show that 1 % of a grape seed extract containing 30 % of procyanidins, significantly increases the survival of T. castaneum at 42 °C when added to flour as a dietary source. The beneficial effects of grape seed extract could not be reproduced by supplementing flour with single catechins of which the oligomeric procyanidins consist. We identified previously stress resistance genes responsible for a survival extension by dietary ingredients and show here by the use of RNA-interference that a knockdown of transcripts encoding homologues of Nrf-2 or Jnk-1 block the effects of grape seed extract on survival. Interestingly, grape seed extract under knockdown of Foxo-1 caused a significant survival reduction, stressing the hormetic response as underlying the survival extension by the dietary interventions. In conclusion, our studies provide evidence that a procyanidin-rich extract is able to extend the survival of the model organism T. castaneum. Catechin monomers, however, appear not to mediate the effects. The active ingredients, moreover, need the presence of stress resistance factors, and here especially of Foxo-1, in order to promote their preventive activities with regard to degenerations.
Keywords: longevity; stress resistance; Tribolium castaneum; food-gene interactions; catechins; ddc:630